Healthy humans with a narrow upper airway maintain patency during quiet breathing by dilating the airway during inspiration. (18th October 2014) - Cheng, Shaokoon; Brown, Elizabeth C.; Hatt, Alice; Butler, Jane E.; Gandevia, Simon C.; Bilston, Lynne E.
Abstract : Key points: During quiet breathing, the muscles of the upper airway of healthy humans contract to dilate the airway during inspiration. We used dynamic tagged magnetic resonance imaging to show that the amount of active upper airway dilatation during inspiration increases as airway cross‐sectional area decreases. Older and more overweight subjects have smaller airways, and this is linked to increased active airway dilatation. These data show that healthy subjects with narrow airways can overcome anatomical risk factors for airway collapse by actively dilating their airways during inspiration. In contrast, obstructive sleep apnoea patients with similarly narrow airways show either little or no dilatory motion during inspiration or abnormal bi‐directional movement. This regulation of airway behaviour fails in these patients. Abstract: A patent upper airway is essential for survival. Increased age, obesity and some upper airway anatomical features are associated with failure to maintain upper airway patency during sleep, leading to obstructive sleep apnoea. However, many healthy subjects with these risk factors do not develop this condition. The aim of this study was to determine how anatomical factors and active dilator muscle contraction contribute to upper airway patency in healthy volunteers across a broad range of age and body mass index (BMI). A 'tagged' magnetic resonance imaging technique quantified respiratory‐related motion of the anterior and lateral walls of the upper airway during quiet breathing in the supine position. Fifty‐two subjects aged 22−68 years with BMI from 17.5 to 40.1 kg m −2 were studied. Higher BMI was associated with smaller airway cross‐sectional area at the level of soft palate ( P  < 0.05). The genioglossus moved anteriorly to dilate the upper airway during inspiration. This movement increased with increasing BMI, increasing age, a smaller airway area, and steeper tongue‐base angle (all P  < 0.05). Motion of the lateral upper airway at the soft‐palate level was variable and less strongly linked to anatomical features of the upper airway. Multiple regression indicated that anterior genioglossus motion decreased with increasing airway area ( P  = 0.03) and with increasing tongue‐base angle ( P  = 0.02). These data suggest that healthy humans, including those whose anatomy places them at increased risk of airway closure, can maintain upper airway patency by dynamically dilating the airway during inspiration.